Treatment of landfill leachate in coagulationflocculation method by using micro zeolite and micro sand - Lee, Mao Rui (2013)
In this study, efficiency of coagulation-flocculation process was evaluated for leachate collected from Pasir Gudang sanitary landfill, Johor, Malaysia. The efficiency of coagulation-flocculation process using micro zeolite and micro sand of different sizes and combined with coagulants and coagulant aids were determined. In addition, the optimum rapid mixing time and speed, slow mixing time and speed, settling time of coagulants, settling time of coagulants with polymer, settling time with polymer and micro zeolite, settling time of coagulants with polymer and micro sand, pH, dose of coagulants, dose of coagulant aids and dose of micro zeolite and micro sand were determined. The efficiency of using polyaluminium chloride (PAC) as a coagulant in the coagulation-flocculation process to remove SS, colour, COD and ammoniacal nitrogen from semi-aerobic leachate as compared with alum and ferric chloride were also determined. PAC showed better removal efficiencies when compared with ferric chloride and alum. The doses of PAC, alum and ferric chloride were fixed at 2000 mg/L in the determination of the efficiency of micro zeolite and micro sand. The highest percentage of removal in SS, colour, COD and ammoniacal nitrogen were 96%, 95%, 58% and 35% for PAC, 89%, 92%, 46% and 26% for alum and 96%, 84%, 37% and 26% for ferric chloride. The leachate was also treated by adding coagulant aids, cationic polymer FO4290 SH and anionic polymer AN934 SH. Cationic polymer FO4290 SH achieved higher percentage of removal of SS, colour, COD and ammoniacal nitrogen compared with anionic polymer AN934 SH. The particle sizes of the micro zeolite and micro sand was divided into 6 categories which were 75µm-90 µm, 91 µm -106 µm, 107 µm -125 µm, 126 µm -150 µm, 151 µm -180 µm and 181 µm -212 µm. The micro zeolite was combined with the coagulant and coagulant aid. The process was repeated by using micro sand. Micro zeolite combination with PAC and cationic polymer (PAC + cationic polymer + micro zeolite) was found to be more efficient in leachate treatment.